Anti-economics the perception of organization and spontaneous order and its impact on public policies - Ábelovský, Adam (2013)
Anti-economics is a fundamental critique of rationality in economics based in misconception of organization and spontaneous order. Some of the anti-economics is based in Folk Economics, mostly laymen. Economists also tend to be wrong when analyzing basic principles of neoclassical economics. These results are not persuasive. Complex character of the human mind - explored through Folk Economics, bounded rationality and Hayek's The Sensory Order -- transfers itself to the study of social phenomena and brings the need for use of subjective or ecological rationality. In the perception of objective rationality there is no incentive for learning and that is in contradiction with Hayek's theory of mind. Neoclassical economics might find common ground with subjective theory of mind in the fields of experimental economics, e.g. neuroeconomics. Hayekian approach to rationality enforces constraints to government and bottom up rules to be maintained.